2010
DOI: 10.1210/me.2009-0357
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of IGF-I Receptor (IGF-IR) in Primary Osteoblasts Reduces GH-Induced STAT5 Signaling

Abstract: GH promotes longitudinal growth and regulates multiple cellular functions in humans and animals. GH signals by binding to GH receptor (GHR) to activate the tyrosine kinase, Janus kinase 2 (JAK2), and downstream pathways including signal transducer and activator of transcription 5 (STAT5), thereby regulating expression of genes including IGF-I. GH exerts effects both directly and via IGF-I, which signals by activating the IGF-I receptor (IGF-IR). IGF-IR is a cell surface receptor that contains intrinsic tyrosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 86 publications
5
32
0
Order By: Relevance
“…Furthermore, the deletion or silencing of IGF-1R in osteoblasts and ␤-cells desensitizes the cells to GH-induced STAT5 activation and downstream gene expression (30 -32). This diminished GH-induced signaling in osteoblasts was specifically rescued by the reexpression of IGF-1R or an IGF-1R lacking most of its ICD (31) but not by an IGF-1R/insulin receptor (IR) chimera in which the regions of the IGF-1R ECD ␣-chain were replaced by those of the related IR (34). These findings suggest that the GHR-IGF-1R interaction via the ECDs allows augmented GH signaling and that the ICD kinase activity of IGF-1R is not required.…”
mentioning
confidence: 99%
“…Furthermore, the deletion or silencing of IGF-1R in osteoblasts and ␤-cells desensitizes the cells to GH-induced STAT5 activation and downstream gene expression (30 -32). This diminished GH-induced signaling in osteoblasts was specifically rescued by the reexpression of IGF-1R or an IGF-1R lacking most of its ICD (31) but not by an IGF-1R/insulin receptor (IR) chimera in which the regions of the IGF-1R ECD ␣-chain were replaced by those of the related IR (34). These findings suggest that the GHR-IGF-1R interaction via the ECDs allows augmented GH signaling and that the ICD kinase activity of IGF-1R is not required.…”
mentioning
confidence: 99%
“…Moreover, we (50) showed that GH could stimulate bone formation even in the global IGF-I KO mice, although not to the extent of IGF-I replacement. Studies by Gan and colleagues showed that GH can promote the formation of GHR/JAK2/IGF-IR complex to facilitate GHR signaling in osteoblasts (71), indicating a novel complementation between GHR and IGF-IR signaling, which could be a basis for some IGF-IR-dependent GH actions. The fact that OCN IGF-IR KO mice failed to respond to GH treatment to increase bone mass suggests that IGF-IR-dependent actions of GH are the predominant responses to promote skeletal anabolism (70).…”
Section: Integration Of Local Igf-i/igf-ir Signaling With Systemic Homentioning
confidence: 99%
“…shown that deletion of IGF-1R markedly inhibits acute GH-induced STAT5 activity, while sparing GH-induced ERK activity in primary osteoblasts (Gan et al, 2010). Similar results on functional collaboration of GHR and IGF-1R but not insulin receptors were obtained in another study on mouse calvarial cells (Gan et al, 2013).…”
Section: Ghr Signalling Crosstalksupporting
confidence: 71%
“…Recently it has been shown that both mitogens have a much closer interaction than previously thought. Huang et al have reported that GH can induce a functional complex between GHR, Jak2 and IGF-1R which is at least partially independent of the kinase activity of IGF-1R (and therefore IGF-1) (Gan et al, 2010). In addition by using a Cre-loxP system these authors have…”
Section: Ghr Signalling Crosstalkmentioning
confidence: 99%